Soft core : a novel - Newell, Brittany, 1994- (Farrar, Straus and Giroux, 2025)
"A stripper's madcap search for her missing ex-boyfriend takes her over the edge in this whip-smart, wildly funny novel about love, sex, work, and sex work"--